Kesiapan dan Motivasi Mahasiswa dalam Mengikuti Pembelajaran Online di Masa Pandemi COVID-19 - Nur Indrianti; Ellen Chung; Ammar Hamid Adil (Graduate School of Universitas Negeri Malang, 2022)
This study aimed to determine online learning readiness, motivation, and challenges for students in Indonesia during the COVID-19 pandemic. Aspects considered in this study included supporting devices and skills to use them, independence in learning, self-control for successful learning, learning motivation, and online communication. The study was conducted using an online questionnaire and crosstabs analysis. The results showed that the students had a good readiness and motivation to do online learning during the pandemic. The most common obstacles included internet connection, limited data quota, unsupported devices, and lecturer learning methods.